Network infrastructure in the present-day realities - Zheleznyak, Olga (project baikal, 2021)
The development of digital technologies, the transformation of the Internet into a “communication medium” leads to the formation of a network society with the large-scale development of network culture and the invasion of network business and network forms of education. Replacement of the face-to-face contact by the network communication, destruction of personal space, openness of personal life, its “inclusion in the network”, simultaneous possibility of anonymity, protection and irresponsibility of users become a reality of modern life. Network systems are becoming the basic infrastructure of modern society.